Mass Transfer Studies on Adsorption of Phenol from Wastewater Using Lantana camara, Forest Waste - C. R. Girish; V. Ramachandra Murty (International Journal of Chemical Engineering)
Adsorption is one of the important treatment methods for the removal of pollutants from wastewater. The determination of rate controlling step in the process is important in the design of the process. Therefore, in the present work, mass transfer studies were done to evaluate the rate-limiting step in the adsorption of phenol from aqueous solution onto Lantana camara. Different mass transfer models were used to find the rate-limiting step and also to find the values of external mass transfer coefficient and diffusion coefficient. The Biot number was found to investigate the importance of external mass transfer to intraparticle diffusion. From the various models studied and the Biot numbers obtained, it was found that the adsorption on Lantana camara was controlled by film diffusion. The sensitivity analysis was performed to study the significance of the model parameters on the adsorption process.